Acute Thrombotic Occlusion of Left Internal Jugular Vein Compressed by Bypass Graft for Thoracic Endovascular Aortic Repair Debranching Procedure - Sim, Hyung Tae (Korean J Thorac Cardiovasc Surg, 2014)
Thoracic endovascular aortic repair has become a widespread alternative treatment option for thoracic aortic aneurysm. The debranching of arch vessels may be required to provide an acceptable landing zone for an endovascular stent graft. We report a case where the bypass graft used in the thoracic endovascular aortic repair procedure compressed the left internal jugular vein, causing acute thrombotic occlusion.